HUBUNGAN POLIMORFISME GEN MELANOCORTIN 4 RECEPTOR (MC4R) RS17782313 TERHADAP DIABETES MELITUS : SEBUAH TINJAUAN NARATIF - Muhammad Rizky Siregar; Anggelia Pupspasari; Citra Maharani; Ahmad Syauqy (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran, 2026)
Melanocortin 4 receptor (MC4R) plays a central role in appetite regulation and energy homeostatis. The rs17782313 polymorphism in the downstream region of MCR4 has been consistently associated with obesity, hyperglycemia and an increased risk of type 2 diabetes mellitus (T2DM), although the magnitude of the effect varies across ethnicities and study design. A largescale meta-analysis indicates that the C risk allele increases the risk of T2DM partially independent of BMI. Literature search on Pubmed, Scopus, Web of Science and Google Scholar; studies in English or Indonesian on the rs17782313 genotype were included, while non-journal publications and studies that did not present genotype data were not included in this review. Cross-ethnic evidence indicates that carriers of the C allele have a 6-10% increased risk of T2DM. In Korean population, the C allele was associated with higher fasting glucose and increase diabetes risk, with differences in effect according to sex and BMI. This was reinforced by a 2023 systematic review reporting an association between rs17782313 and increase BMI, waist circumference and glucose. The MC4R rs17782313 polymorphism is thought to act as a genetic susceptibility marker for DM, particularly T2DM. Large-scale cohort studies and functional studies are needed to confirm the causal relationship and clarify the interaction between genetic and environmental factors.